The adolescent Internet Adaptability Scale: Development and psychometric properties - Weijun Wang; Jianmei Ye; Rouchun Dong; Shihao Ma; Dawei Huang; Xin Zhao (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
This study presents the development and validation of the Adolescent Internet Adaptability Scale (AIAS), designed to assess adolescents’ adaptive capacities in Internet use. The scale development encompassed multiple phases with diverse sample sizes: item pool generation through interviews (n = 15), scale structure analysis via Exploratory Factor Analysis (EFA, n = 553) and Confirmatory Factor Analysis (CFA, n = 4,637), along with reliability (n = 4,637) and validity (n = 4,637) analyses. The reliability phase included alpha, composite reliability, and retest reliability (n = 132), while the validity phase covered structural, convergent, discriminant, criterion-related validity, and measurement invariance tests. The AIAS, comprising eight dimensions—Internet curiosity, Internet self-efficacy, Internet learning ability, Internet socialization ability, Internet information search ability, Internet information protection ability, Internet self-control ability, and Internet positive coping ability—demonstrates strong reliability and validity. It shows positive correlations with Internet use—parental active help, well-being, and meaning in life, and negative correlations with Internet addiction and depression, with stronger associations observed with positive indicators. These findings highlight the Internet’s potential as a platform for strength acquisition. The AIAS, with its comprehensive nature, is promising for tailoring adolescent support from a positive psychology perspective, enabling holistic assessment and targeted interventions. It also advances understanding of youth development in the digital era, proving valuable for clinical and research applications. Ongoing evaluation, cross-cultural validation, and longitudinal research are essential for realizing its full potential. This multidimensional scale significantly advances the assessment of adolescent Internet use, equipping stakeholders to effectively address adolescents’ digital behaviors for enhancing well-being.